Analisis Strategi Iklan Royco “Formula Baru Dengan Rasa Ayam 50% Lebih Kuat” Tahun 2024 Dalam Menarik Perhatian Konsumen - Marcella Dea Yunike; M. Rehan Mayandri; Diva Nasywa Ramadhani; Mukhsin Patriansah (VisArt: Jurnal Seni Rupa dan Design, 2026)
This study begins with the problem of how the Royco advertisement version "New Formula with 50% Stronger Chicken Flavor! Makes Different Hands, Same Taste!" attracts consumers' attention through the visual and verbal elements displayed. This study uses a qualitative method with a descriptive approach. The analysis was carried out by describing the elements of the advertisement, such as visuals, color, and narrative, then examining their role in each stage of AIDA. Data were obtained through observations of the Royco advertisement version "New Formula with 50% Stronger Chicken Flavor! Makes Different Hands, Same Taste!" in 2024. The results show that the Royco advertisement successfully implemented the AIDA model effectively through appetizing food visuals, clear product messages, and memorable slogans. Saussure's semiotic analysis shows that the color, packaging, character expressions, and the claim "50% Stronger Chicken Flavor" contain meanings that strengthen the product's image as a practical, delicious, and trusted cooking spice. The conclusion of the study shows that the Royco advertisement version "New Formula with 50% Stronger Chicken Flavor! Makes Different Hands, Same Taste!" Royco is effective in attracting consumer attention through the application of the AIDA model and the use of meaningful visual and verbal cues. These elements successfully build a product image that is delicious, practical, and high-quality, and encourage consumer interest in using and purchasing Royco products